MO161: Comparison of Therapeutic Plasma Exchange with Centrifugation and Filter Technique with a Focus on Efficacy, Safety, Platelet Loss and Patients' Comfort. (3rd May 2022) - Frimmel, Silvius; Mitzner, Steffen; Hinz, Michael; Westphal, Christina; Winkelmann, Alexander; Koball, Sebastian
Abstract: BACKGROUND AND AIMS: Therapeutic plasma exchange (TPE) is an established therapy in the treatment of various immunologic kidney and neurological diseases. Humoral factors as antibodies, complement factors, cytokines and immune complexes, which all are assumed to play a role in demyelinating or inflammatory disorders as multiple sclerosis, can be eliminated. TPE has been implemented into therapeutic guidelines of a broad spectrum of neurological diseases [1 –3 ]. Centrifugal (cTPE) and membrane-based (mTPE) are the methods of choice for TPE. Head to head studies comparing both methods are scarce and patients' comfort has not yet been investigated [4 –7 ]. Our aim was to compare cTPE (Spectra Optia™, TerumoBCT) with mTPE (multiFiltrate™, Fresenius Medical Care) with a focus not only on safety and efficacy parameters but also on patients' comfort with the present monocentric, prospective and randomized crossover study. This is, to the best of our knowledge, the first study addressing patients' comfort comparing both systems. METHODS: The study was conducted as an open-label prospective trial with a cross-over design comparing cTPE using the Spectra Optia™ (Terumo BCT, Lakewood, CO, USA), and mTPE using the multiFiltrate™ with the plasmafilter plasmaFluxP2dry™ (Fresenius Medical Care, Bad Homburg, Germany). The first two treatments were performed within the study for each patient: one with the Spectra Optia and one with the multiFiltrate. Duration of set-up and priming of the devices, total procedure time, blood flow, total plasma volume exchanged, volume of the removal bag, volume of the anticoagulant and the type of vascular access were documented. Laboratory parameters such as IgG, IgA, IgM, fibrinogen, white blood cell, red blood count and thrombocytes were documented before and after treatment. Data from the first two treatments were documented. The differences of the parameters were compared using the Wilcoxon matched-pairs signed-rank or Mann-Whitney (U) test. RESULTS: A total of 26 patients (17 women /9 mem) were included in the study and 52 treatments were documented. A median of 3000 mL of plasma was treated; the median duration of the procedure was 117 min (cTPE) versus 154 min (mTPE) ( P  = .03). Despite removal of fibrinogen ( P  = .04), no significant differences were found for the removal IgG ( P  = .09), IgM ( P  = .18) and IgA ( P  = .57). Both methods were equally effective. Erythrocyte loss was higher with mTPE ( P  = .003), platelet loss tended to be higher with mTPE, but without reaching a level of significance ( P  = .22; Table 1 ). The results of the patient questionnaire are shown in Figure 1 . CONCLUSION: Both procedures can be performed safely with comparable results regarding parameters of quality as fibrinogen, IgG, IgM and IgA with a trend to better elimination with cTPE. Comparing the duration of the procedure, cTPE was significantly superior to mTPE. An advantage regarding cell loss (RBC) was seen for cTPE, platelet loss tended to be higher with mTPA, but without statistical significance. Finally, as a result of shorter duration, patients' comfort was significantly higher with cTPE.